A framework based on fuzzy AHP-TOPSIS for prioritizing solutions to overcome the barriers in the implementation of ecodesign practices in SMEs. Issue 6 (18th August 2019) - Singh, P. K.; Sarkar, P.
ABSTRACT: Small and medium enterprises (SMEs) are under pressure to adopt sustainable practices in their business due to increasing environmental challenges. This study aims to identify and prioritize the solutions to overcome the barriers in the implementation of ecodesign practices in SMEs. This study helps the companies to develop and implement the strategies on priority using higher ranked solutions. In this study, a framework is proposed that is based on fuzzy analytical hierarchy process and fuzzy technique for order preference by similarity to ideal solution to rank the solutions that overcome the barriers in ecodesign implementation in SMEs. The proposed framework is illustrated by conducting a case study of an Indian ring and piston manufacturing company. This framework provides an effective support in the decision-making of the company for producing eco-friendly products through the implementation of ecodesign practices. Results of this study emphasize that training of designers to use different ecodesign tools is an essential practice for SMEs.